2022
DOI: 10.3389/fspor.2022.963946
|View full text |Cite
|
Sign up to set email alerts
|

Pre-season body composition has minimal influence on in-season match availability, and match performance in female Australian Football League (AFLW) players

Abstract: This study examined the relationship between pre-season body composition, in-season match performance, and match availability in female players competing in the Australian Football League Women's (AFLW) competition. With the outlawing of body composition assessments as part of pre-draft player evaluations in the AFLW, this study seeks to examine whether this is justified. Twenty-two (n = 22) players had body composition assessed with dual-energy x-ray absorptiometry at the beginning of the 2021 AFLW pre-season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Thus, decreased body fat percentage may enhance a developing kicker’s ability to coordinate their limbs by achieving better positioning on their stance leg and movement of the swing leg during the kicking action. Conversely, one study in elite senior female AF players (AFLW) reported no significant differences for body composition characteristics and kicking efficiency [ 54 ]. This may be explained by biological maturation influences on kinanthropometric variables and physical fitness attributes in young athletes, with early maturation often demonstrating higher kinanthropometric values and better physical fitness performance results [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreased body fat percentage may enhance a developing kicker’s ability to coordinate their limbs by achieving better positioning on their stance leg and movement of the swing leg during the kicking action. Conversely, one study in elite senior female AF players (AFLW) reported no significant differences for body composition characteristics and kicking efficiency [ 54 ]. This may be explained by biological maturation influences on kinanthropometric variables and physical fitness attributes in young athletes, with early maturation often demonstrating higher kinanthropometric values and better physical fitness performance results [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of body composition, specifically fat-free mass (FFM), in athletes is an important component of optimizing health, well-being, and sport performance (12). Higher levels of FFM and lower relative fat mass (FM) have been shown to be associated with physical attributes relating to sport performance (8) (i.e., strength, speed, power) (27,29,33) and a reduced risk of injury (4,28); therefore, FFM accrual is often a primary goal for athletes engaged in strength and conditioning programs for their respective sport (2,13,29). Although FFM is considered an important parameter of sport performance, absolute measures of FFM do not account for differences in height and body stature, making direct comparisons across sports and sport positions challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Several years later, this method was used to identify potential anabolic-androgenic steroid use in resistance-trained men and to determine a potential natural upper limit of FFM accrual, relative to height (22). More recently, FFMI has been used to characterize FFM among athletes and to establish normative values in men and women athletes across a variety of sports and sport divisions (5,10,14,28). For example, previous work has noted average FFMI values of 18.73-24.94 kg•m 22 (9,14) across a range of National Collegiate Athletic Association (NCAA) Division (D) II and DIII men athletes and values of 15.3-20.09 kg•m 22 (7,9,19) among diverse samples of DI, DII, and DIII women athletes.…”
Section: Introductionmentioning
confidence: 99%